Strength from within: Exploring self-compassion among frontline nurses during the COVID-19 pandemic - Condes, Kristine A.; Lachica, Toni-An B.; ajera, Sheilla M. Tr; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
Frontline nurses during the COVID-19 pandemic have faced significant psychological and emotional burdens. This study explored how self-compassion supported their resilience in high-stress healthcare settings. Using a qualitative phenomenological design, ten nurses from public and private hospitals in the Philippines were interviewed via Zoom. Participants described their experiences working in COVID-19 units or similarly demanding areas, and how they coped with uncertainty, fear, and fatigue. Thematic analysis revealed four key insights: Fire from Within: A Fuel to Win, Passion to Care: Above and Beyond the Fear, Recreation: A Key to Reset and Reconnect, and Silver Lining: An Effective Coping Mechanism. These themes illustrated how nurses cultivated self-kindness, emotional balance, and purpose amid a crisis. Self-compassion emerged not only as a coping mechanism but also as a sustaining force for professional commitment. The study recommends institutional support through targeted mental health programs and policy reforms. Promoting self-compassion among nurses is essential for protecting their well-being and preparing the workforce for future health emergencies.